2014
DOI: 10.1155/2014/152075
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Gelsolin Levels Decrease in Diabetic State and Increase upon Treatment with F-Actin Depolymerizing Versions of Gelsolin

Abstract: The study aims to map plasma gelsolin (pGSN) levels in diabetic humans and mice models of type II diabetes and to evaluate the efficacy of gelsolin therapy in improvement of diabetes in mice. We report that pGSN values decrease by a factor of 0.45 to 0.5 in the blood of type II diabetic humans and mice models. Oral glucose tolerance test in mice models showed that subcutaneous administration of recombinant pGSN and its F-actin depolymerizing competent versions brought down blood sugar levels comparable to Sita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…rhuGSN is a recombinant form of pGSN having a similar structure and function as pGSN [18]. It is well established that the level of pGSN declines in a variety of ailments such as inflammation, diabetes, trauma, sepsis, rheumatoid arthritis, and multiple sclerosis [15,16,21,31], and exogenous rhuGSN supplement/replacement therapy effectively rescues the affected animals from inflammation [15,32], sepsis [9,22], burn [33], diabetes [16], and thrombosis and pulmonary thromboembolism [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…rhuGSN is a recombinant form of pGSN having a similar structure and function as pGSN [18]. It is well established that the level of pGSN declines in a variety of ailments such as inflammation, diabetes, trauma, sepsis, rheumatoid arthritis, and multiple sclerosis [15,16,21,31], and exogenous rhuGSN supplement/replacement therapy effectively rescues the affected animals from inflammation [15,32], sepsis [9,22], burn [33], diabetes [16], and thrombosis and pulmonary thromboembolism [17].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma gelsolin (pGSN) thus plays a critical role in severing and clearing actin filaments released into the bloodstream after any tissue injury [14]. In addition, gelsolin levels have been stated to decline in a plethora of diseases, and supplementing exogenous recombinant human gelsolin (rhuGSN) alleviated distress symptoms in many disease conditions including sepsis, inflammation, diabetes [15,16], thrombosis, and pulmonary thromboembolism [17]. Interestingly, cytoplasmic gelsolin (cGSN) can bind to globular actin to nucleate its polymerization and surprisingly can also bind to filamentous actin to break and cap it back to monomeric actin form [12,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that a high plasma glucose level could induce actin cytoskeleton disruption [22]. This is asserted to relate apoptotic cell death [25]. That is why F-actin could release from cell to plasma when cell injury is occurred [10].…”
Section: Discussionmentioning
confidence: 99%
“…Apolipoprotein A1 and APOC3 levels were elevated in the heart, but they are expressed in the liver and intestine and apparently their cardiac accumulation accompanied the influx of lipids and cholesterol to the heart [59][60][61]. Decreased levels of gelsoline indicates pathological conditions as this protein normally occurs in high amounts and is extensively degraded when binding to filamentous actin (released upon cell death or rupture) occurs [62]. This protein mitigates the detrimental effects of systemic inflammation [63], thus gelsoline downregulation could potentiate a greater impact of obesity-related inflammation on the system.…”
Section: The Cardiac Outcomes Of Obesity Reflect Systematic Disturbancesmentioning
confidence: 99%